A study of Indigenous children’s developmental outcomes: the impact of child, family and socio-economic characteristics - Redmond, G; Mullan, K (My University, 2011)
Closing the gap in early child development between Indigenous and non-Indigenous children is a core aim of Federal, State and Territory Governments. Addressing this aim raises a complex set of issues and yet, all too often, Indigenous people and families are simply regarded as a single unitary group. This is unfortunate, as efforts to close the gap stand a much better chance of success if they are based on a more nuanced understanding of the relationship between disadvantage and child development within Indigenous communities. This paper offers a small step towards a better understanding of the relationship between child development outcomes and characteristics associated with the child, family, the broader environment and socio-economic conditions. Using data from the first wave of the Longitudinal Study of Indigenous Children we present a detailed picture of the characteristics of Indigenous children, their primary carers, their environment, and aspects of the socio-economic conditions within which they develop. Focusing on Indigenous children 3-6 years old, we look at associations between these characteristics and outcomes relating to children’s readiness to learn, their early language development, and their socio-emotional development. Our results show a complex set of relationships and we discuss implications for policy development and future research.
Keywords: Child Development; Childhood and child development; Child Development; Childhood and child development